Canada : Economic Developments and Policies. (IMF Staff Country Reports; Country Report, 1995)
This paper examines economic developments and policies in Canada during 1990-95. Spurred by the robust growth in the United States and the easing of monetary conditions between 1991 and 1993, economic growth in Canada continued to strengthen during 1994. Real GDP grew by 4.5 percent in 1994 after growing by 2.2 percent in 1993 and 0.6 percent in 1992. Economic growth in 1994 was led by exports and investment in machinery and equipment. However, growth was more broadly based in 1994; private consumption strengthened, and there was a rebound in residential and nonresidential construction.